2001
DOI: 10.1046/j.1523-1755.2001.0590051850.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic potassium depletion induces renal injury, salt sensitivity, and hypertension in young rats

Abstract: Dietary potassium deficiency per se increases the BP in young rats and induces salt sensitivity that may involve at least two different pathogenic pathways: increased RAS activity and induction of tubulointerstitial injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
45
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 33 publications
7
45
0
2
Order By: Relevance
“…32 Eventually, peritubular capillaries are permanently damaged and reduced in number, thus causing ischemia, increasing the oxidative stress, and mediating tubulointerstitial inflammation and impairment of pressure diuresis. In support of this hypothesis, a reduction in peritubular capillary density was demonstrated in experimental models of SSHTN [33][34][35] and in humans with essential hypertension. 36 Hypertension and tubulointerstitial inflammation Although not emphasized in the 1958 classical study of Sommers et al, 27 inflammatory infiltration was a constant feature in the renal biopsies of hypertensive patients and, more importantly, the authors did note 'collections of lymphocytes' in the renal interstitium in about 20% of the hypertensive patients that had minimal or no arteriolar changes.…”
Section: Renal Microvascular Disease and Interstitial Inflammation Armentioning
confidence: 63%
“…32 Eventually, peritubular capillaries are permanently damaged and reduced in number, thus causing ischemia, increasing the oxidative stress, and mediating tubulointerstitial inflammation and impairment of pressure diuresis. In support of this hypothesis, a reduction in peritubular capillary density was demonstrated in experimental models of SSHTN [33][34][35] and in humans with essential hypertension. 36 Hypertension and tubulointerstitial inflammation Although not emphasized in the 1958 classical study of Sommers et al, 27 inflammatory infiltration was a constant feature in the renal biopsies of hypertensive patients and, more importantly, the authors did note 'collections of lymphocytes' in the renal interstitium in about 20% of the hypertensive patients that had minimal or no arteriolar changes.…”
Section: Renal Microvascular Disease and Interstitial Inflammation Armentioning
confidence: 63%
“…Dietary potassium restriction stimulates the release of renal renin and AngII (13,14). AngII exerts its physiological effects by binding to AT1 and AT2 receptors.…”
mentioning
confidence: 99%
“…Pere et al (29,30) reported that a high-potassium diet (2.4% potassium) is renoprotective in cyclosporine-induced nephrotoxicity, compared with a diet containing 0.8% potassium. In contrast, chronic potassium depletion causes renal functional deterioration, interstitial nephritis, or cyst formation in animals and humans (3,4,6,11,32,34,40,47). The proposed underlying mechanisms of the deleterious effect of potassium depletion include activation of the local renin-angiotensin II system (RAS) (32), increased angiotensin II receptor (AT 1 ) expression (12), and altered activity of the sodium-potassium pump in the renal tubule (35), acting by blood pressure-dependent and/or blood pressureindependent mechanisms.…”
mentioning
confidence: 99%